PENGARUH PENERAPAN E-SPT, PENGETAHUAN, SOSIALISASI, KESADARAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN MELAPORKAN PAJAK UMKM DI KOTA SEMARANG - Wery, Artiany; Rahmadhani, Sari (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
The purpose of this study was to examine and analyze the effect of the application of e-SPT, Tax Knowledge, Tax Socialization, Taxpayer Awareness and Tax Sanctions on Tax Reporting Compliance (Case Study on MSMEs in Semarang City). This study uses a survey method with quantitative data obtained by distributing research questionnaires directly and indirectly to 250 respondents as MSME taxpayers and using a Likert scale of 1-7. The data analysis technique used multiple linear regression analysis technique. The results of this study indicate that the application of e-SPT has a positive effect on tax reporting compliance and Tax knowledge has no effect on tax reporting compliance. Tax socialization has no effect on tax reporting compliance, Taxpayer awareness has a positive effect on tax reporting compliance and Tax Sanctions have a positive effect on tax reporting compliance.